2012
DOI: 10.1371/journal.pntd.0001617
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence, Features and Risk Factors for Malaria Co-Infections amongst Visceral Leishmaniasis Patients from Amudat Hospital, Uganda

Abstract: Background and methodologyDue to geographic overlap of malaria and visceral leishmaniasis (VL), co-infections may exist but have been poorly investigated. To describe prevalence, features and risk factors for VL-malaria co-infections, a case-control analysis was conducted on data collected at Amudat Hospital, Uganda (2000–2006) by Médecins sans Frontières. Cases were identified as patients with laboratory-confirmed VL and malaria at hospital admission or during hospitalization; controls were VL patients with n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
54
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(63 citation statements)
references
References 34 publications
5
54
1
Order By: Relevance
“…This is in agreement with the study which is conducted in India 5.9% among Indian patients with fever and splenomegaly [16]. However, this prevalence was lower as compared to study reported in Uganda 19% [25]. This variation might be due to difference in the VL and malaria prevalence which is 21.6% and 11.7% in this study and 57% and 31% in Uganda, respectively [25].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…This is in agreement with the study which is conducted in India 5.9% among Indian patients with fever and splenomegaly [16]. However, this prevalence was lower as compared to study reported in Uganda 19% [25]. This variation might be due to difference in the VL and malaria prevalence which is 21.6% and 11.7% in this study and 57% and 31% in Uganda, respectively [25].…”
Section: Discussionsupporting
confidence: 91%
“…A similar finding was also reported in other studies [2527]. The higher prevalence rate might be due to the fact that males engage in activities which make them more prone to infective mosquito and sand fly bites as compared to females who are mostly at home and protected from such infective bites.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In East African endemic regions, VL and malaria share the same geographical distribution [19], thus co-infections of VL and malaria are common in several countries, including Sudan [36]. It has recently been shown that malaria co-infections manipulate immune responses of co-infected hosts[37].…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a distinction was made between those NTDs that are thought to be controllable at the population level by means of mass drug administration (e.g., five to six rounds of albendazole plus ivermectin administered to all community members aged five years and above against lymphatic filariasis) and preventive chemotherapy (e.g., annual treatment of school-aged children with praziquantel against schistosomiasis) on one hand, and, on the other hand, those NTDs that involve individual case finding and management (e.g., Buruli ulcer) [9]. Recently, increasing attention has been given to the issues of co-endemicity, coinfection, and comorbidity [1012], but generally, binary thinking prevails with regard to the identification, management, control, and elimination of NTDs. It should be noted, however, that for the patients suffering from those problems, the specific causal pathogens are of lesser importance.…”
Section: Challenge #1: Binary Thinking and Syndromic Management Of Ntdsmentioning
confidence: 99%